2017
DOI: 10.1016/j.ssresearch.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying, perceived job stressors, and psychological distress: Gender and race differences in the stress process

Abstract: A large body of empirical research documents the adverse mental health consequences of workplace bullying. However, less is known about gender and race differences in the processes that link workplace bullying and poor mental health. In the current study, we use structural equation modeling of survey data from the 2010 Health and Retirement Study (N = 2292) and draw on stress process theory to examine coworker support as a buffering mechanism against workplace bullying, and gender and race differences in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 61 publications
(49 reference statements)
4
73
1
5
Order By: Relevance
“…aspects of workload and ambiguity, powerlessness and vulnerability, and lack of control over one's work situation (α = .78). Several studies have shown a positive association between perceived job stressors and workplace bullying (Attell, Kummerow Brown, & Treiber, 2017;Lewis et al, 2017).…”
Section: Stress Exposure (Woseq)mentioning
confidence: 99%
“…aspects of workload and ambiguity, powerlessness and vulnerability, and lack of control over one's work situation (α = .78). Several studies have shown a positive association between perceived job stressors and workplace bullying (Attell, Kummerow Brown, & Treiber, 2017;Lewis et al, 2017).…”
Section: Stress Exposure (Woseq)mentioning
confidence: 99%
“…Scholars maintain that bullying can happen to any individual in any context, where there are actual or perceived power imbalances (Attell, Kummerow‐Brown, & Treiber, ; Misawa, ). Sedivy‐Benton, Strohschen, Cavazos, and Boden‐McGill () suggest that bullying incidents (subtle and blatant) occur frequently.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
“…Attell et al () suggested that women are impacted by workplace bullying more than their male counterparts. The authors posited that “this disparity indicates that gender is a critical factor in how workplace bullying manifests and how employees interpret that bullying” (Attell et al, , p. 212). Findings revealed that males received more protection from co‐worker social support than did females.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
“…Stress is also a reason for the aggressive behavior of a person, and stress also leads to the negative behavior of an employee at the workplace (Ferris, Brown, Berry, & Lian, 2008). Due to stress, an employee cannot make good relationships in the workplace, and he will not find a friendly environment in the workplace because of stress ( Attell, Kummerow, & Treiber, 2017;Turner & Turner, 2013). Stress negatively affects the mental health of the person and individual want social support when he suffers stress situation, also emotional and physical help from the other in a stress situation.…”
Section: Stressmentioning
confidence: 99%
“…The workplace ostracism also enhances the negative emotion of an individual such as mental illness, depression, sadness, jealousy, shame, guilt, embracement. These all emotions lead an individual towards stress; the stress situation minimizes the self-awareness of an individual a person doesn't know how to react in a present situation (Attell, 2017). The workplace ostracism also has a negative impact on employee engagement at the workplace because of ostracism; the communication gap will be increased between the employees (Saver, 2011).…”
Section: Relationship Between Workplace Ostracism Stress and Employementioning
confidence: 99%